Experiences of the homeless accessing an inner-city pharmacy and medical student-run clinic in Johannesburg - Deanne Johnston; Patricia McInerney; Hilary Thurling (AOSIS, 2020)
Background: Mental and physical health problems are both contributory factors and drivers of homelessness. Adding to this, the homeless encounter numerous barriers when accessing healthcare services. Aim: The aim was to determine the experiences of the homeless when accessing healthcare services and the reason why they visit Trinity Health Services (THS). Setting: Trinity Health Services, a student-run clinic (SRC) based at an inner-city church in Johannesburg, South Africa, provides free acute healthcare services to the homeless. Methods: This qualitative study comprised three focus group discussions (FGDs) with the homeless who access services provided by the church. Those who had previously visited THS on at least one occasion were invited to participate in FGDs. The FGDs were audio-taped and transcribed verbatim. The data were analysed thematically using Tesch's eight steps. Results: Three themes were identified. The first theme, homelessness affecting health, explains how limited access to food, ablution facilities and shelter negatively impact their well-being. This led to the second theme, health needs, where tuberculosis, influenza, sexually transmitted diseases and dental infections were identified as ailments occurring frequently. The need for healthcare services was explicit, yet participants were reluctant when accessing healthcare services as they faced stigma and discrimination. The third theme, THS in addressing health needs, denotes the value of THS in the community it serves where they were treated with compassion and empathy. Conclusion: The needs of this homeless community as well as the role played by THS were clearly identified. However, THS provides limited services, and integration with existing healthcare services is essential.